G347(P) Implementing clinical pathways in a paediatric emergency department. (12th March 2018) - Konig, B; Meades, N; Gupta, A; Cheung, R
Abstract : Background: Despite the fact that evidence based guidelines are widely available adherences to them remains unsatisfactory. 1 Embedding guidance and decision support into clinical work processes at the bedside might improve this. Aim: We turned eight existing clinical guidelines into 'clinical pathways' embedded in paediatric Emergency Department (ED) workflow, which obviates the need to learn or look up a guideline, and gives clinical decision support at the bedside. We hypothesise that this would improve guideline compliance and reduce unwarranted clinical variation. Methods: Clinical pathways were created for the most common and/or important presentations to paediatric ED, namely 'The Wheezy Child under 5 years of age', 'Diarrhoea and Vomiting under 5', 'Child with Stridor', 'Febrile convulsion', 'Asthma in over 5's', 'The Child with a limp', 'Non-blanching rash', 'The child with fever and cough'. Activation of the pathway is symptom- rather than disease-based, and the pathway forms part of the ED clinical notes. The pathway guides clinician decision making, from treatment and investigations options (including reminders of unnecessary or non-evidence-based interventions); criteria for discharge, referral and admission; and patient information. Results: Pathways were well received and comprehensively implemented. At time of writing, clinical outcomes are available for four of the pathways. Results include reduction of the inappropriate use of nebulisers from 75% to 25%, reduced reattendances from 29% to 0%; more appropriate use of prednisolone and reduced requests for chest x-rays (for wheeze); increased urine sampling from 28% to 52% and more appropriate admissions and halved reattendance rates for diarrhoea and vomiting; reduced reattendances from 22% to 0% for stridor; reduced admission rate from 75% to 40% for febrile convulsion. Conclusion: The creation of clinical pathways, embedding existing clinical guidelines into routine care processes, have improved guideline adherence, improved clinical outcomes and reduced clinical variation. Reference: . Runnacles J, Roueche A, Lachman P. Arch Dis Child Educ Pract ED 2017;0:1–7. doi:10.1136/archdischild-2017-312740